CUSTOMER SERVICE SYSTEM ADMINISTRATION AGENCY ABCS - Antriani Br Purba; Yulina, Skom., MMSI Yulina, Skom., MMSI (Jurnal Sistem Informasi, 2005)
Computer Use in the administration of companies, particularly in the consolidated customer data and transaction data is something very important to the company as a distributor of newspapers and magazines, as a material for storing customer data and transaction data, then the computer is necessary.To the writer tries to give a customer information system design activity continues to be quickly and precisely then created a customer data processing program with applications programming language Visual Basic 6.0. with computerized data expected, it can be processed correctly, quickly and accurately.